O devir-monstro em O Rosto de Um Outro, de Abe Kôbô - Ichikawa, Jovanca Kamizi (2020)
Originally published in 1964, The face of another novel, by Abe Kôbô, tells the story of a man who lost his face in a work accident. Since then, the deformity, the anguish in not feeling part of society anymore and, mainly, the conflict with his wife, lead him to build a mask from the face of another. In a first moment, the reader is invited to see this “faceless” character as a monstrous, bitter and selfish figure, because he registers in his manuscripts the deepest and most complex feelings, aggressively. Although the work is marked by the face, by the mask and by the double, this research sought to highlight the becoming-monster, because it understood that the novel provides a necessary reading about the anomalous, about the other. The becoming-monster is understood as a real perception of the character, of what he feels. A way of escaping in a limiting shape of himself. In view of this, the present study aimed to understand how the “loss” of the face led this individual to other perceptions, and thus to understand this link as a trigger for the becoming and the double that arise from the confessions and accounts that the character leaves in manuscripts directed to his wife. To compose the discussion and analysis of the work, the assumptions used were from FREUD (1919); RANK (1925); ROSSET (1976); DELEUZE and GUATTARI (1977, 1980); COURTINE and HAROCHE (1988); LE BRETON (1992, 2015); GIL (1994). Based on these authors, a reading was constructed having as theoretical contribution the concepts of face, mask, becoming and double. Still within this narrative, this study approached three other aspects: the importance of written language in the work, the “transtextuality” that mark a rich narrative and the “phantasmagorical pact”. The latter resumes the author, when the fictional narrative is haunted by revealing ghosts of the individual, and this may be Abe himself. The methodology used was descriptive bibliographic research, with a qualitative approach. As a result, the work presents a “deterritorialized” man who manifests a becoming-monster and protagonizes a double, admittedly stimulated by a society of appearances and judgments. A “monster discourse” which then led to a reflection on a society of masks.